306 Anterior Cruciate Ligament Graft Rupture: Analysis of Anteromedial Versus Trans-Tibial Portal Technique for Femoral Tunnel Placement in 473 Patients. (4th May 2021) - Al-Hourani, K; Shepperd, J; Sripathmanathan, K; Zhang, Y; Hull, B; Murray, I R; Duckworth, A D; Keating, J F; White, T O
Abstract: Introduction: Correct femoral tunnel position in anterior cruciate ligament reconstruction (ACLR) is critical in obtaining good clinical outcomes. We aimed to delineate whether any difference exists between the anteromedial and trans-tibial portal femoral tunnel placement techniques on the primary outcome of ACLR, graft rupture. Method: Adult patients (>18 years old) who underwent primary ACLR between January 2011 - January 2018 were identified and divided based on portal technique (anteromedial v trans-tibail). The primary outcome measure was graft rupture. Univariate analysis was used to delineate association between independent variables and outcome. Binary logistic regression was utilised to delineate odds ratios of significant variables. Results: 473 patients were analysed. Median age at surgery was 27 years old (range 18-70). 152/473 (32.1%) patients were anteromedial group compared to 321/473 (67.9%) trans-tibial. 25/473 (5.3%) patients sustained graft rupture. Median time to graft rupture was 12 months (IQR 9). A higher odd for graft rupture was associated with the anteromedial group, which trended towards significance (OR 2.03; 95% CI 0.90 - 4.56, p = 0.081). Conclusions: There is no statistically significant difference in ACLR graft rupture rates when comparing anteromedial and trans-tibial portal technique for femoral tunnel placement. There was a trend towards higher rupture rates in the anteromedial portal group.